Navigation ability before and after menopause: Epidemiology / Risk and protective factors in MCI and dementia. (7th December 2020) - Chapin, Benjamin Albert; Khondoker, Mizanur; Coughlan, Gillian; Spiers, Hugo; Hornberger, Michael
Abstract: Background: Cognitive decline is a common complaint in menopause. Alzheimer disease(AD) has higher incidence in women and early menopause increases risk for AD. Studies of cognitive change at menopause have had mixed results. Navigational ability declines early in the course of AD. No studies have looked at changes in navigational ability around menopause. Objective: Determine the effect of menopause on navigation. Method: Participants were 200, 999 persons aged 35‐65 who downloaded the Sea Hero Quest app and completed enough levels to analyze navigation. Measures of navigation examined included distance traveled and time spent to complete levels as well as accuracy in determining one's starting point after completing a maze. These scores were normalized based on early, simple levels in order to control for video game ability. Each measure was analyzed by splitting male and female participants into ages 35‐45 and ages 55‐65 in order to look at persons before and after menopause. Groups were analyzed using a 2‐way ANOVA with gender and age as independent variables. Additionally, piecewise linear modeling was applied to the entire population aged 35 to 65 to test whether there was a significant change in the slope of decline in navigational ability at age 51, the average age of menopause. Result: Female gender and advancing age were both predictive of worse performance on all measures. ANOVA found significant(p<0.001) but small effect sizes for an age by gender interaction with partial eta 2 for distance = 0.002, duration < 0.001 and flare accuracy <0.001. Piecewise linear modeling found small but significant (p<0.001) changes in slope of worsening scores in distance, duration and flare accuracy at age 51. The increased rate of worsening performance was actually greater in men than women. Conclusion: While men had better navigational performance than women at all ages, there is not a substantial change in this gap following menopause. Additionally, the relative rate of decline in female performance actually decreased relative to males at the typical age of menopause. This study suggests that natural menopause is unlikely to have a significant negative effect on navigational ability.